2017
DOI: 10.4018/joeuc.2017100103
|View full text |Cite
|
Sign up to set email alerts
|

Sentiment Analysis of Tweets for Estimating Criticality and Security of Events

Abstract: Social Media has become one of the major industries in the world. It has been noted that almost three fourth of the world's population use social media. This has instigated many researches towards social media. One such useful application is the sentimental analysis of real time social media data for security purposes. The insights that are generated can be used by law enforcement agencies and for intelligence purposes. There are many types of analyses that have been done for security purposes. Here, the autho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 9 publications
0
18
0
Order By: Relevance
“…Results showed that the accuracy of the unsupervised approach and lexicon-based approach could achieve 80.68% and 75.20%, respectively. Subramaniyaswamy et al [21] used a lexicon approach of sentiment analysis to predict possible violent events in the future from tweets. However, they only analyzed three proportions of sentiments: positive, negative, and neutral.…”
Section: Related Workmentioning
confidence: 99%
“…Results showed that the accuracy of the unsupervised approach and lexicon-based approach could achieve 80.68% and 75.20%, respectively. Subramaniyaswamy et al [21] used a lexicon approach of sentiment analysis to predict possible violent events in the future from tweets. However, they only analyzed three proportions of sentiments: positive, negative, and neutral.…”
Section: Related Workmentioning
confidence: 99%
“…Different experiments have been performed on social network data to clarify their user's behaviour and to establish various comprehensive management plans [16]. In addition, Sentiment analysis is one of the most relevant strategies utilized today in various disciplines in our lives [17] relying on supervised machine learning strategies cantered on dataset evaluation. Our research aims to empower social networking functionalities and integrate it with the Internet-of-Things technology to analyse tweets simultaneously to categorize sentiment of specific users.…”
Section: Iiiv Sentiment Analysis Techniques For Social Mediamentioning
confidence: 99%
“…After analyzing various clustering algorithms, we have proposed a min-cut clustering algorithm for keyphrase extraction [29]. For persuasive recommendation, a travel plan is created based upon active target user, user id and location [30] [33]. Many types of wearable sensor devices contain unobtrusive sensors, smart textiles and printable electronic tattoos for health detection [31].…”
Section: Graph Modelsmentioning
confidence: 99%